A new curvularin glycoside and its cytotoxic and antibacterial analogues from marine actinomycete Pseudonocardia sp. HS7. Issue 10 (18th May 2016) - Ye, Xuewei; Anjum, Komal; Song, Tengfei; Wang, Wenling; Yu, Siran; Huang, Haocai; Lian, Xiao-Yuan; Zhang, Zhizhen
Abstract : Five curvularin macrolides (1 –5 ) were isolated from the cultured broth of marine actinomycete Pseudonocardia sp. HS7 that was obtained from the cloacal aperture of sea cucumber Holothuria moebii . The structures of these isolates were characterized as (11 S, 15 R )-11-hydroxycurvularin (1 ), (11 R, 15 R )-11-hydroxycurvularin (2 ), curvularin-7- O -α-D -glucopyranoside (3 ), trans -dehydrocurvularin (4 ) and curvularin (5 ) based on their NMR and HRESIMS data as well as chemical degradation. Compound3 is a new macrolide with a rare α-D -glucopyranose substituent. Compounds1 –4, 5a and5c (the acyl products of5 ), suppressed the proliferation of all six tested cancer cell lines and4 is the most active compound with IC50 values ranging from 0.59 to 3.39 μM. The 11-hydroxycurvularins1 and2 also showed antibacterial activity inhibiting the growth of Escherichia coli . Abstract :